Biological activity of the lipopeptide-producing Bacillus amyloliquefaciens PGPBacCA1 on common bean Phaseolus vulgaris L. pathogens - Torres, María Julia; Perez Brandan, Carolina; Sabate, Daniela Constanza; Petroselli, Gabriela; Erra Balsells, Rosa; Audisio, Marcela Carina (2018)
Bacillus amyloliquefaciens PGPBacCA1 was studied regarding its aptitude to protect common bean seeds from their intrinsic pathogens. Also, the inhibition of different environmental phytopathogenic fungi was tested. Two cultivars of Phaseolus vulgaris L. were evaluated: cv. Nag (black bean) and cv. Alubia (white bean). Aspergillus spp., Penicillium spp. and Fusarium spp. constituted the natural fungal biota of both seeds, whereas white bean and black bean also exhibited Cladosporium spp. and Rhizopus spp., respectively. B. amyloliquefaciens PGPBacCA1 prevented the development of the endophytic fungi of black bean, while only Cladosporium spp. survived in the white variety. Growth chamber assays were carried out and bacilli cells were applied on seeds without affecting neither the vigor nor the germination potential of either type of bean. In addition, B. amyloliquefaciens PGPBacCA1, by dual cultures, was able to inhibit the development of the following phytopathogenic fungi: Sclerotium rolfsii (35%), Sclerotinia sclerotiorum (76.5%), Rhizoctonia solani (73%), Fusarium solani (56.5%), and Penicillium spp. (71.5%). The UV-MALDI TOF MS analysis showed that B. amyloliquefaciens PGPBacCA1 co-produces different homologues of the lipopeptides surfactin, iturin and fengycin in the presence of S. sclerotiorum and F. solani. These compounds were identified as the main responsible for the antagonistic effect. SEM analysis confirmed the antifungal effects of the lipopeptides, which also caused damage to chlamydospores and sclerotia of Fusarium and Sclerotinia, respectively. B. amyloliquefaciens PGPBacCA1 can thus be applied to these bean seeds varieties as a potential bioprotection agent.